College Students’ Psychological Well-Being during the Covid-19 Pandemic: An Investigation Based on Students’ Gender and Education Level - Farozin, Muh.; Purnama, Diana Septi; Astuti, Budi; Prasetya, Arif Budi; Nurbaiti, Anifa Tuzzuhroh (Jurnal Kajian Bimbingan dan Konseling, 2022)
This study aims to determine the level of psychological well-being based on gender and level of education being pursued during the Covid-19 pandemic. Participants are students from various faculties and postgraduate programs from diploma, undergraduate, professional education, masters and doctoral education levels in Yogyakarta, Indonesia. The instrument used is the Ryff Psychological Well-Being Scale which has been adapted by Engger with a content validity value of CVR equal to 1 which is in the good category and reliability is 0.935 in the good category. The data analysis used was Mann-Whitney non-parametric statistics for the different test of psychological well-being based on sex, and Kruskal Wallis as a different test for the level of education being pursued. The results showed that there was no significant difference based on gender, while based on the level of education on psychological well-being there were differences. The results of this study can be taken into account in the development of guidance and counseling programs and services for college students.